Cardiac involvement in patients 1 year after recovery from moderate and severe COVID-19 infections - Qiao, Jinhan; Zhao, Peijun; Lu, Jianyao; Huang, Lu; Ma, Xiaoling; Zhou, Xiaoyue; Xia, Liming (Frontiers in Cardiovascular Medicine, 2022)
Background Some patients suffered persistent cardiac symptoms after hospital discharge following COVID-19 infection, including chest tightness, chest pain, and palpitation. However, the cardiac involvement in these patients remains unknown. The purpose of this study was to investigate the effect of COVID-19 infection on the cardiovascular system after 1 year of recovery in patients hospitalized with persistent cardiac symptoms. Materials and methods In this prospective observational study, a total of 32 patients who had COVID-19 (11 diagnosed as severe COVID-19 and 21 as moderate) with persistent cardiac symptoms after hospital discharge were enrolled. Contrast-enhanced cardiovascular magnetic resonance (CMR) imaging was performed on all patients. Comparisons were made with age- and sex-matched healthy controls (n = 13), and age-, sex- and risk factor-matched controls (n = 21). Further analysis was made between the severe and moderate COVID-19 cohorts. Results The mean time interval between acute COVID-19 infection and CMR was 462 ± 18 days. Patients recovered from COVID-19 had reduced left ventricular ejection fraction (LVEF) (p = 0.003) and increased extracellular volumes (ECVs) (p = 0.023) compared with healthy controls. Focal late gadolinium enhancement (LGE) was found in 22 (68.8%) patients, mainly distributed linearly in the septal mid-wall or patchily in RV insertion point. The LGE extent in patients with severe COVID-19 was higher than that in patients with moderate COVID-19 (p = 0.009). Conclusion This 1-year follow-up study revealed that patients with persistent cardiac symptoms, after recovering from COVID-19, had decreased cardiac function and increased ECV compared with healthy controls. Patients with COVID-19 predominately had a LGE pattern of septal mid-wall or RV insertion point. Patients with severe COVID-19 had greater LGE extent than patients with moderate COVID-19.